The practice of enterprise modeling : 11th IFIP WG 8.1. Working Conference, PoEM 2018, Vienna, Austria, October 31-November 2, 2018, Proceedings /: 11th IFIP WG 8.1. Working Conference, PoEM 2018, Vienna, Austria, October 31-November 2, 2018, Proceedings. (2018) - Unknown
No abstract available